2012
DOI: 10.1016/j.ijid.2012.05.327
|View full text |Cite
|
Sign up to set email alerts
|

Hazard and risk mapping of malaria disease in Iran: An 11 year trend

Abstract: Illness) surveillance.Methods: The surveillance activities include the epidemiology and virology aspect. Each PHCs collects the specimens from ILI cases and send the specimens to designated laboratory.Results: The types of seasonal influenza are Influenza A and Influenza B. The subtypes of Influenza A are H1N1 and H3N2, but since 2010 the subtypes of seasonal influenza is add by the H1N1pdm09. Since 2007, in the average of the proportion number of influenza A each year around 15 -20%, while influenza B around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Because the success rate of measles vaccination is 90–95%, some people are unwilling to receive measles vaccination, especially those who belong to the vulnerable groups of society. [ 10 ] If appropriate preventive interventions are not conducted, outbreaks may happen in the future. In a study investigating the risk of measles outbreaks in Iran, it was suggested that drastic measures should be taken to improve relevant health care indexes in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Because the success rate of measles vaccination is 90–95%, some people are unwilling to receive measles vaccination, especially those who belong to the vulnerable groups of society. [ 10 ] If appropriate preventive interventions are not conducted, outbreaks may happen in the future. In a study investigating the risk of measles outbreaks in Iran, it was suggested that drastic measures should be taken to improve relevant health care indexes in Iran.…”
Section: Introductionmentioning
confidence: 99%